Diversifikasi Pangan : Solusi Krisis Pangan ditengah Pandemi COVID 19 - M Rahayu; M Taufik; M Tufaila; R Haski; A Asniah (JURNAL KARYA PENGABDIAN, 2020)
The COVID-19 pandemic and long drought were caused significant disruption to supply food and distribution agricultural products. Production has slowed down have become a challenge by the government, Agriculture of Ministry, research, academic, and farmer. Team social services-PPDM Wolasi village made a food diversification plot. The method that was used technical guidance and making demonstration plots as a solution for food insecurity. Partners respond well to the knowledge and technology transfer was given. The land has planted with various commodities such as upland rice, corn, chili, tomatoes, vegetables and the manufacture of catfish ponds: the catfish ponds that have 7 m long, 5 m wide, and 0.8 m deep. This model of food diversification  believed to be a solution to food insecurity in the region.